U.S. social welfare reform policy transitions from 1981 to the present - Caputo, Richard K. (Springer eBooks., 2011)
Nearly half a century after Lyndon Johnson coined the phrase, America continues to fight the war on poverty, especially as such modern realities as the global economy, job outsourcing, and the recession contribute to the numbers of the unemployed and the working poor. As social welfare and reform efforts are debated in Congress and local agencies, facts regarding past programs are often elusive. U.S. Social Welfare Reform examines the evolution of major Federal cash assistance programs to low-income families, from the advent of the Reagan administration to the early Obama years. Written for the professional (but not requiring expertise in quantitative analysis to understand it), it details which programs succeeded, analyzes why others failed, and highlights the need for further reform in the context of today's economic climate. This volume: Traces the changes from the Federal/state open entitlement AFDC program to the state-run, time-limited TANF initiative. Explores the development of the Earned Income Tax Credit program. Features two sets of National Longitudinal Survey data on EITC-eligible families. Includes original results of outcome studies of youth participating in job training and education programs. Evaluates the Obama administration?s social policy initiatives in meeting the challenges of the current recession. Revisits previously rejected policies that would benefit low-income working families. The uniqueness of its scope and presentation suits U.S. Social Welfare Reform to researchers in family relations, family sociology, economics of the family, and social policy, whether the task at hand is reviewing past events or charting a future course of action.